2016
DOI: 10.1007/s10040-016-1388-9
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeological properties of fault zones in a karstified carbonate aquifer (Northern Calcareous Alps, Austria)

Abstract: This study presents a comparative, field-based hydrogeological characterization of exhumed, inactive fault zones in low-porosity Triassic dolostones and limestones of the Hochschwab massif, a carbonate unit of high economic importance supplying 60 % of the drinking water of Austria's capital, Vienna. Cataclastic rocks and sheared, strongly cemented breccias form low-permeability (<1 mD) domains along faults. Fractured rocks with fracture densities varying by a factor of 10 and fracture porosities varying by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 72 publications
2
41
0
1
Order By: Relevance
“…KAGIS detected only small increments of porosity around 731 masl, and so, it can be considered that variation in this parameter in Mela aquifer is not important and there are no depths with different hydrodynamic behaviours. These values match with the characteristic value of pore volume in karst aquifers as it has been shown in other studies (Bauer, Schröckenfuchs, & Decker, 2016;Różkowski & Różkowski, 2016).…”
Section: Modelled Resultssupporting
confidence: 90%
“…KAGIS detected only small increments of porosity around 731 masl, and so, it can be considered that variation in this parameter in Mela aquifer is not important and there are no depths with different hydrodynamic behaviours. These values match with the characteristic value of pore volume in karst aquifers as it has been shown in other studies (Bauer, Schröckenfuchs, & Decker, 2016;Różkowski & Różkowski, 2016).…”
Section: Modelled Resultssupporting
confidence: 90%
“…Bauer et al (2016) concluded that, on a regional scale, faults of a particular deformation event have to be viewed as forming a network of flow conduits directing recharge more or less rapidly towards the water table and the springs. In addition, these faults are very important in influence positively on groundwater occurrences and acting as transmission routs in the limestone bodies' conduits for transporting and storing the included groundwater.…”
Section: Curve Types and Fault Zone Determinationmentioning
confidence: 99%
“…Nevertheless, it is inadequate for a full understanding of individual local relationships. Only a detailed consideration of different degrees of fracturing (Čar, 1982Bauer et al, 2016) can yield sufficient information to enable interpretations of the dimensions and shaping of particular phenomena, their dependence upon structural controls (especially the degree of fracturing) and the history of their genesis.…”
Section: Structural Mappingmentioning
confidence: 99%